Half-quantum vortices: Квантованные вихри и турбулентность - Mineev, V.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Unlike to superfluid 4He the superfluid 3He-A support the existence of vortices with half-quantum of circulation as well as single quantum vortices. The singular single quanta vortices as well as nonsingular vortices with 2 quanta of circulation have been revealed in rotating 3He-A. However, the half-quantum vortices in open geometry always possess an extra energy due to spin-orbit coupling leading to formation of domain wall at distances larger than dipole length ~10–3 cm from the vortex axis. Fortunately the same magnetic dipole–dipole interaction does not prevent the existence of half-quantum vortices in the polar phase of superfluid 3He recently discovered in peculiar porous media “nematically ordered” aerogel. Here we discuss this exotic possibility. The discoveries of half-quantum vortices in triplet pairing superconductor Sr2RuO4 as well in the exciton–polariton condensates are the other parts of the story about half-quantum vortices also described in the paper.